Predictors of Psychological Distress Trajectories in the First Year After a Breast Cancer Diagnosis - Park, Jin-Hee; Chun, Mison; Jung, Yong-Sik; Bae, Sun Hyoung (Asian nursing research, 2017)
Psychological distress is a significant and ongoing problem for breast cancer. These mental health problems are often neglected as they are not always properly understood. This study was performed to explore the trajectory of psychological distress over 1 year since breast cancer surgery and to identify the associated factors for the trajectory. One hundred seventeen women who underwent surgery for breast cancer completed the psychological distress thermometer and problem lists from after surgery to 12 months after surgery. Information on their sociodemographic and clinical characteristics was also obtained. Group-based trajectory modeling was performed to identify the distinct trajectories of psychological distress. Chi-square test and logistic regression analysis were performed to determine predictors of psychological distress trajectories. A two-group linear trajectory model was optimal for modeling psychological distress (Bayesian information criterion = -777.41). Group-based trajectory modeling identified consistently high-distress (19.4%) and low-decreasing distress (80.6%) trajectories. Old age, depression, nervousness, and pain were significant predictors of consistently high-distress trajectory. Our results indicate that distinct trajectory groups can be used as a screening tool to identify patients who may be at an increased risk of psychological distress over time. Screening for psychological distress during disease diagnosis is important and necessary to identify patients who are at an increased risk of elevated distress or at risk of experiencing psychological distress over time.